Analisis Rantai Pasok dan Strategi Pengembangan Susu Kambing Pasteurisasi di Goatzilla Farm & Cafe - Nurlita Lailia; Mohammad Rondhi; Djoko Soejono (Forum Agribisnis, 2020)
Goatzilla Farm & Cafe is agroindustry in Lumajang which processes goat milk into various products and has several business units that related to enduro goat farms. The main product of Goatzilla Farm and Cafe is pasteurized goat milk. the scale of goat milk pasteurized production is still small category because the labour used is labour in the family, the supply of fresh goat milk is uncertain, and product marketing is still limited due to BPOM's permit constraints. Therefore, it is necessary to make efforts to develop pasteurized milk products at Goatzilla Farm & Cafe. This research aims to determine supply chain, value-added, and development strategy of goat pasteurized milk at Goatzilla Farm & Cafe. The location of the research was determined by the purposive method. The research method used descriptive and analytic methods. The result of the research showed that the links involved in the supply chain of pasteurized goat milk are Goatzilla farm units, partner farmers, collectors, the processing unit of Senduro Goatmilk Indonesia, Goatzilla Farm & Cafe, Senduro Goatmilk Indonesia outlet, and consumers. The processing of fresh goat milk into pasteurized goat milk provides positive value-added and can be classified as a medium category. The recommended strategy for the development of pasteurized goat milk based on the FKK value of the highest driving and inhibiting factors is to form a cooperative business entity engaged in agribusiness of Senduro goat milk.